Modelo Prolab: “EcoPad, proyecto ecosostenible de producción de lana PET aplicando economía circular en Lima” - Young Lores, Daniel Antonio (2024)
Ecopad is a business model created through the Design Thinking process that offers a sustainable and cost-effective construction material. The relevant social issue addressed is the limited accessibility to quality and sustainable construction materials for the D and E sectors in Metropolitan Lima. Therefore, recycled PET wool is proposed as an insulating material within a system of partition walls in homes with more suitable attributes, economic accessibility, and environmental sustainability. The value proposition demonstrates competitive advantages over the current market, surpassing brick walls in terms of economic efficiency, construction times, maneuverability, seismic safety, and sustainability. However, the success of the business model depends on overcoming the existing bias towards lightweight materials for partition walls. Thus, training, communication, and awareness campaigns of marketing strategies will be crucial. Additionally, the cost savings for real estate construction companies represent 21%, and an 88% reduction in weight, impacting the structural cost of construction. The collection of raw materials will be carried out through a network of organized recyclers and agreements with real estate companies, providing economic and environmental sustainability, as well as a social focus to the business model by offering dignified and more stable employment to recyclers. The circular economy of the business model not only focuses on economic sustainability but also on reputation through social and environmental responsibility. Therefore, our shareholder's Net Present Value (NPV) is $1,608,803.66, and the social NPV is $51M.